Electrical Power distribution status in West Africa: Assessment and Perspective Overview - (:unkn) unknown (My University, 2019)
This paper deals with the presentation of some of the issues and perspectives of electrification in West Africa. Due to poverty and technological weakness, the electrical grid is made of a dispersed low density of consumption points, in a very vast geographical area. Many solutions including Renewable Energy Source (RES) intended to solve the access to energy for people have been implemented. But common solutions in terms of power availability and quality are not effective, especially in rural areas. The opportunity given by renewable energy resources integration, is not yet effective, considering novelty of the approaches of distributed generation and micro grid applications. The inventory of operational power plants and the planned ones in West Africa is discussed. A state of the art of the potentialities of microgrid (MG) thought as efficient solutions to those issues in the literature are presented.
Keywords: African Research